x → ∞ lim lo g x ( x 2 + 1 − x 2 − 1 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
= = = x → ∞ lim lo g x ( x 2 + 1 − x 2 − 1 ) x → ∞ lim lo g x ( x 2 + 1 + x 2 − 1 2 ) x → ∞ lim [ lo g x ( 2 ) − lo g x ( x ) − lo g x ( 1 + x 2 1 + 1 − x 2 1 ) ] − 1
Problem Loading...
Note Loading...
Set Loading...
L = x → ∞ lim lo g x ( x 2 + 1 − x 2 − 1 ) = x → ∞ lim ln x ln ( x 2 + 1 − x 2 − 1 ) = x → ∞ lim x 1 − ( x 2 + 1 ) ( x 2 − 1 ) x = x → ∞ lim − x 4 − 1 x 2 = x → ∞ lim − 1 − x 4 1 1 = − 1 A ∞ / ∞ case, L’H o ˆ pital’s rule applies. Differentiate up and down w.r.t. x Divide up and down by x 2